Strand 1: Supporting Networked Learning as a whole: Pedagogy, Management and the Learning Environment - Banks, Bob (Proceedings of the International Conference on Networked Learning, 1998)
This paper describes a prototype online Learning Environment supporting open and distance learning. The environment was developed to meet key pedagogical and management requirements which are described here and which were ascertained through the 'Learning Environment Club' - a collaboration involving eleven Further Education Colleges. The most distinctive aim has been to provide a model and overall online support for the whole enterprise of student-centred, flexible learning. The degree of support provided by the Learning Environment for an effective and flexible pedagogical model is discussed. In particular, constructivist and dialogue-oriented views of learning are considered. This is used to focus an analysis of how online environments in general can fully support effective pedagogies. In addition, critical success factors for the introduction of this kind of technology to an institution are discussed.